FEET TROPHIC CHANGES DEPENDENCE OF THE LOWER EXTREMITIES ARTERIES DEFEAT - Волошин О. М., (World of Medicine and Biology, 2015)
Critical limb ischemia is the most severe form of peripheral arterial occlusive disease and is characterized by a high risk of limb loss and high mortality. Recently, vascular surgeons all over the world are increasingly attracted angiosome concept of critical limb ischemia diagnosis and. To date, it remains poorly understood relationship affected ateroslerozis angiosome with blood-perfused portion of the foot, as well as changes in the characteristics necrobiotic few angiosomes occlusion.The prospective study examined characteristics of the foot trophic changes in 60 patients with femoro-popliteal-tibial arterial atherosclerotic lesions segments that were treated at the Zaporizhzhya regional center of vascular and endovascular surgery. The analysis identified a number of angiograms topographic anatomical features. The most common atherosclerotic lesions infrapopliteal celebrated in the pool area of the anterior tibial artery (ATA), especially in the distal parts of it - 20 cases (33.3%) or a combination of destruction ATA and posterior tibial artery (PTA) - 18 cases (30%). Isolated occlusion PTA observed in 12 patients (20%). The combination of lesions PTA and fibular arteries (FBA) in 7 cases (11.6%). Isolated defeat in the pool FBA was found in 3 patients (5%).In assessing foot trophic changes, also identified a number of features. The most common necrobiotic changes occurred on the back surface of the distal portions of the foot and toes - in 29 patients (48.4%). In 15 cases (25%) revealed trophic changes on the plantar surface of the foot in the projection of 2-5 metatarsals. In 8 patients (13.3%) necrosis occurred on the plantar foot surface 1 in the projection of the first finger. In 8 patients (13.3%) had trophic changes in the heel area. Thus, the concept of blood supply angiosome effective and affordable method for topical diagnosis and targeted treatment for patients with critical limb ischemia. Further clinical studies is needed on surgical treatment angiosome arteries, as well as to compare the results of treatment with the "standard" types of surgeries.Trophic changes foot location in critical lower limb ischemia corresponds to the affected segment of arterial blood supply angiosome responsible for this zone. In diffuse lesions of lower extremity arterial bed with hemodynamically significant stenosis of the proximal femoral or iliac artery, necrobiotic changes on the foot may not correspond to the affected angiosomes. Peroneal artery is rarely affected atherosclerotic process in 5% of cases, due to its anatomical features, and trophic changes in line with its angiosome observed in 3% of patients.
Keywords: angiosomes concept; critical ischemia